Comrade Tito, it's all your fault! : Yugoslav citizens' letters to Josip Broz Tito - Jović, Dejan (Array, 2021)
Between 1945 and 1967, Josip Broz Tito, the Marshal and President of Yugoslavia, ‎received 411,769 letters written by citizens of his country. Until 1964 ‎he personally read most of the letters addressed to him and made decisions‎ on requests and comments expressed in them. In this article we argue that ‎Tito used the letters received to establish a direct link between himself and ‎citizens. This was one of the key instruments of his power, as he used letters ‎to conduct a permanent ‘anti-bureauratic revolution’ which would squeeze ‎lower-level officials into a sandwich between him and ‘the people’. We focus ‎on one particular letter, written by Dragomir Katić, a 27-year old unemployed ‎person from Kraljevo, Serbia. The letter arrived in February 1967, and Tito ‎used this occasion to personally meet Katić. Despite Tito’s promise, however, ‎Katić’s problem could not be solved for more than two years, due to a power‎ struggle between Tito and local officials in Serbia. This case sheds new light ‎on the nature of Tito’s alleged absolute power in Yugoslavia. It tells us much‎ about the attitude of dissatisfied individuals in Communist Yugoslavia, who ‎cared much more about solving their personal problems than about changing‎ the system, at least for as long as Tito was alive.‎